The Poisson Quasi-Maximum Likelihood Estimator : A Solution to the “Adding Up” Problem in Gravity Models - Arvis, Jean-François; Shepherd, Ben (Taylor and Francis, 2013)
This article shows that the Poisson Quasi-Maximum Likelihood (QML) estimator applied to the gravity model produces estimates in which, summing across all partners, actual and estimated total trade flows are identical. Other methods such as OLS do not have this desirable property. Indeed, Poisson is the only QML estimator that preserves total trade flows. This result is an additional reason for preferring Poisson as a workhorse gravity model estimator.